Influence of post-annealing temperature on the morphological, structural and optical properties of spin coated zinc oxide thin films - Chaithanatkun, Natpasit; Fujihara, Takeshi; Kamano, Masaru; Konishi, Tomoya; Uehara, Nobutomo; Onlaor, Korakot; Tunhoo, Benchapol; Kozai, Takanori (My University, 2017)
In this study, zinc oxide films were fabricated on quartz glass substrate using spin coating technique with 2 molar of zinc oxide in organic solvent as starting materials. The fabricated sample was post-annealed at different temperature from 350 °C to 750 °C for 60 minutes. The energy dispersive x-ray spectroscopy (EDS) confirmed that zinc oxide coating film was fabricated on the quartz glass substrate. The crystallography of zinc oxide films were analyzed by X-ray diffraction (XRD). The crystallite size of zinc oxide nanoparticles was determined from the full-width at half maximum (FWHM) of XRD peaks using Debye-Scherrer's equation and showed that the zinc oxide films had highly crystalline quality in hexagonal wurtzite crystal structure. The morphological property of films was observed by scanning electron microscopy (SEM). Surface morphology of films shows regularly spread all of zinc oxide films. The optical property of various zinc oxide films was measured using UV-Visible spectrophotometer.
Keywords: Post-annealing temperature; Spin coating technique; Zinc oxide